Exploring Customer-Centric Energy Service Innovation & Development - Berger, Moritz; Lundberg, Melker (My University, 2025)
Facing challenges in the context of digitalization in Sweden’s energy sector, tradi- tional firms are moving towards providing services and solutions to their customers, distancing themselves from the traditional utility-driven perspective. This study explores how digitalization enables customer-centric service innovation and devel- opment by viewing the customer as an active participant in the process and by using the benefits derived from digital customer touchpoints. Using a qualitative approach, semi-structured interviews were held with energy service providers and their customers to gather insights into customer engagement, digital interactions, and market actors. The findings show that customers are being increasingly included in the service in- novation and development process, positioning them as active co-creators of value. Respondents discussed that customers engage both explicitly through active touch- points such as online customer panels and webinars, and implicitly through passive touchpoints from which usage data and behavioral patterns can be derived. Ac- cordingly, digital touchpoints were categorized into passive and active based on the degree of provider involvement in interactions. The study also found that digital- ization is changing the actor constellations in the energy sector. These changes pose challenges for traditional energy service providers since they shift the use of digital touchpoints to various degrees, reducing the possibilities for co-creative innovation and development. Despite these challenges, the study highlights that effective man- agement of digital touchpoints and customer co-creation enhance service innovation and development. By matching digital touchpoints to customers based on their behavior, needs, and preferences they can be used more efficiently when includ- ing customers in the process of innovation and development. Therefore the thesis concludes that energy service providers should take a more structured approach re- garding digital customer touchpoints to match these to the needs of the customer. In this the categorization into active and passive digital touchpoints and implicit or explicit customer engagement may prove helpful.
Keywords: Digitalization, Service Innovation & Development, Energy Services, En- ergy Sector, Digital Touchpoints, Customer Centricity.